2009
DOI: 10.1111/j.1750-3841.2009.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Cocoa Antioxidant Activity, Total Polyphenols, Flavan‐3‐ols, and Procyanidin Content in Foods Prepared with Cocoa Powder

Abstract: Little is known about the effects of common cooking processes on cocoa flavanols. Antioxidant activity, total polyphenols (TP), flavanol monomers, and procyanidin oligomers were determined in chocolate frosting, a hot cocoa drink, chocolate cookies, and chocolate cake made with natural cocoa powder. Recoveries of antioxidant activity, TP, flavanol monomers, and procyanidins ranged from 86% to over 100% in the chocolate frosting, hot cocoa drink, and chocolate cookies. Losses were greatest in the chocolate cake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 27 publications
6
26
0
Order By: Relevance
“…agrotec., Lavras, v. 37, n. 3, p. 244-250, maio/jun., 2013 metabolites such as phenolic compounds (SOUZA et al, 1999). Another important point to be considered is the pre-processing (fermentation, drying and roasting) of cocoa, which according to some authors reduces the concentration of these kind of compounds (ADAMSON et al, 1999;STAHL et al, 2009). Furthermore, the concentration of phenolic compounds varies according to cultivar employed and also the type of chocolate produced (MILLER et al, 2006;PAYNE et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…agrotec., Lavras, v. 37, n. 3, p. 244-250, maio/jun., 2013 metabolites such as phenolic compounds (SOUZA et al, 1999). Another important point to be considered is the pre-processing (fermentation, drying and roasting) of cocoa, which according to some authors reduces the concentration of these kind of compounds (ADAMSON et al, 1999;STAHL et al, 2009). Furthermore, the concentration of phenolic compounds varies according to cultivar employed and also the type of chocolate produced (MILLER et al, 2006;PAYNE et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In one study, polyphenol content of cocoa powder was not substantially affected by preparation techniques used to make chocolate frosting, hot cocoa beverage, or chocolate cookies; however, after undergoing baking in a chocolate cake, natural cocoa powder retained only 5% of its epicatechin content and 54% of its antioxidant activity measured by ORAC. The reason for this is likely the increase in pH caused by the addition of baking soda (244).…”
Section: B Effects Of Food Processing On Flavonoidsmentioning
confidence: 99%
“…Cocoa, the main ingredient of chocolate, is rich in antioxidants, mainly flavonoids (Nehling 2012). Food products prepared with cocoa powder were reported to have high antioxidant activity, total polyphenols, flavanol monomers, and procyanidin oligomers (Stahl et al 2009). Lecumberri et al (2007) studied a fibre-rich cocoa product and found that this product is not only rich in antioxidants but also is suitable to use as an ingredient to enrich low-calorie foods with dietary fibre (Table 1).…”
Section: Sources Of Adfmentioning
confidence: 99%